Effect of Child-to-Child Approachon Practices of Primary School Children Regarding Epileptic Seizures First Aids (Medico Legal Update, 2021)
Background:Many studies showed that epileptic seizures occur more commonly in childhood stage. Mostchildren epileptic seizures occur, during the school day. During this seizure, the child requires immediatefirst aid for an epileptic seizure. Aim: The study aimed to evaluate the effect of Child-to-Child Approach ofPrimary School Children Regarding Epileptic Seizures First Aids. Design: A quasi – experimental design(one group pre and posttest) was used in this study. Setting: This study was conducted at six governmentalprimary schools at Ismailia city. Sample: A multi-stage random sample was used in this study,the totalnumber of children was180 (both male & female)divided into two groups. Trained children group (12 child)and intervention group (168 child). Tools: Two tools were used. First tool: Interviewing questionnaire wasdeveloped by the researcher and included three parts: Socio demographic data, knowledge about epilepticseizure and its first aid measures,Students’ attitudes toward epileptic seizures. Second tool: PracticalChecklist: it was used to assess the practice of student’s in relation of first aids of epileptic seizures basedon the Camfield et al., (2019).The Results: Showed that there were statistically significant increases in mean scores ofknowledgesofstudying sample about epileptic seizure.And showed that there were highly statistically significant increasesin mean scores ofpractices. The results showed that there were statistically significant increases in meanscores of positive attitudes as well as the total score.Conclusion: The knowledge,practice, and attitude of primary school children about first aid of epilepticseizure were improved post implementation of the program compared to pre implementation of the program.Recommendation: Continuous Child-to-Child Approach for Primary School Children about first aid ofepileptic seizure.